The role of the school as an incubator of local and international creativity - Sahar Al-Qawasmeh (مجلة رابطة التربويين الفلسطينيين للآداب والدراسات التربوية والنفسية, 2024)
This research investigates the pivotal role of educational institutions in cultivating creativity among students, recognizing its significance beyond traditional artistic domains to encompass essential innovative and collaborative skills crucial for success in contemporary workplaces. Emphasizing the integration of creativity across various subjects, the study advocates for a holistic approach that permeates all aspects of school education, moving away from isolated art projects towards a comprehensive pedagogical framework. Central to the inquiry is the exploration of creativity within the context of Palestinian education, eschewing rigid definitions to underscore its fundamental importance as a life skill rather than an optional pursuit. Particularly during the Senior Cycle, instilling a creative mindset is deemed essential, positioning creativity at the heart of learning to enrich the educational journey. Drawing on insights from consultations with stakeholders, the research underscores the ongoing necessity for concerted efforts in embedding creativity within the educational landscape. Recommendations are formulated to foster creativity both locally and globally, advocating for collaboration with initiatives such as Creative Youth and alignment with creative industry strategies. By establishing environments conducive to nurturing and celebrating creativity, schools can equip students with the skills necessary for thriving in a dynamic and interconnected world.